Thermodynamic modelling of the lead sintering roasting process - Rojas Sánchez T.; Serrano Romero A.; Ramírez Hernández A.; López Rodríguez J.; Almaguer Guzmán I.; Benavides Pérez R.; Flores Favela M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This work proposes a simulation strategy of the lead sintering process assuming that it takes place in a horizontally moving packed bed with transverse air flow. Some local chemical reactions occur at rates that depend on the temperature, and chemical species formed in one volume stage will flow for further reaction in other stages. To simulate this process, the model reactor is divided into a number of sequential stages. Condensed species flow horizontally, and gaseous species leave each stage vertically. The compositions and temperatures of the species are calculated considering that the local thermodynamic equilibrium is reached in each stage without external heat transfer, apart from the gas flow, before moving on to the next stage. The model calculates the temperature profile along the sintering machine, the compositions of the sinter and the exhaust gas. The results of the proposed model were compared with sinter pot experimental trials and a reasonably good agreement was obtained. This model can be used to optimize the operating conditions of the lead sintering process.